2019
DOI: 10.1002/bab.1754
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol protects against myocardial ischemia and reperfusion injury by activating transcription factor EB (TFEB)

Abstract: Although cilostazol was proved to have antitumor biological effects, its function in myocardial ischemia and reperfusion (I/R) injury and the underlying mechanisms were not fully illustrated yet. In this study, a rat model of I/R injury was constructed and quantitative real-time PCR, Western blot, and immunofluorescence (IF) assay were performed. Our results showed that cilostazol increased LC3 II/LC3 I ratio, reduced p62 abundance, and promoted the expressions of LAMP1, LAMP2, cathepsin B, and cathepsin D, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For example, sustain-releasing H 2 S donor 5-(4-methoxyphenyl)-3H-1, 2-dithiole-3-thione [ 155 ], metformin [ 271 ], and sevoflurane precondition [ 272 ] restore the impaired autophagic flux induced by MI/RI through AMPK activation, thus protecting the myocardium from MI/RI. Intermittent fasting [ 273 ] and cilostazol [ 274 ] protect against myocardial ischemia/reperfusion injury by transcription factor EB-mediated transcriptional initiation of autophagy-lysosome mechanisms. Transient hypoxia can also protect against reperfusion injury by slightly upregulating autophagy [ 275 ].…”
Section: Interventions Targeting Oxidative Stress and Related Pathways In Myocardial Reperfusionmentioning
confidence: 99%
“…For example, sustain-releasing H 2 S donor 5-(4-methoxyphenyl)-3H-1, 2-dithiole-3-thione [ 155 ], metformin [ 271 ], and sevoflurane precondition [ 272 ] restore the impaired autophagic flux induced by MI/RI through AMPK activation, thus protecting the myocardium from MI/RI. Intermittent fasting [ 273 ] and cilostazol [ 274 ] protect against myocardial ischemia/reperfusion injury by transcription factor EB-mediated transcriptional initiation of autophagy-lysosome mechanisms. Transient hypoxia can also protect against reperfusion injury by slightly upregulating autophagy [ 275 ].…”
Section: Interventions Targeting Oxidative Stress and Related Pathways In Myocardial Reperfusionmentioning
confidence: 99%
“…In myocardial ischemia and reperfusion injury, cardiomyocyte death can be caused by lysosomal consumption, which manifests as a decrease in the number of lysosomes and the downregulated expression of LAMP-1 139 . Both the enhancement of lysosomal function and promotion of autophagy were reportedly beneficial by alleviating cardiomyocyte death after myocardial ischemia and reperfusion injury 139,143 . In proteotoxic cardiomyopathy, cardiomyocytes showed impaired autophagic flux and reduced lysosome abundance; however, adeno-associated virus-TFEB transduction was sufficient to reverse cardiomyopathy pathology in a preclinical study 142 .…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Cilostazol, as a selective inhibitor of phosphodiesterase-3, has been known for increasing intracellular cAMP levels [12,13]. While Bai Y et.al reported that cilostazol can attenuate superoxide production and reduce the infarct size in rabbit by activating CTSB [14].…”
Section: Ivyspringmentioning
confidence: 99%